One‐Flask Synthesis of Cyclic Diguanosine Monophosphate (c‐di‐GMP). Issue 4 (11th April 2023) - Gaffney, Barbara L.; Jones, Roger A.
Abstract: The bacterial signaling molecule cyclic diguanosine monophosphate (c‐di‐GMP) plays a key role in controlling biofilm formation and pathogenic virulence, among many other functions. It has widespread consequences for human health, and current research is actively exploring its molecular mechanisms. The convenient one‐flask, gram‐scale synthesis of c‐di‐GMP described here has facilitated these efforts and has been applied to a variety of analogs. © 2023 The Authors. Current Protocols published by Wiley Periodicals LLC.